Familial classification of the Boraginales. Issue 3 (24th June 2016) - Luebert, Federico; Cecchi, Lorenzo; Frohlich, Michael W.; Gottschling, Marc; Guilliams, C. Matt; Hasenstab-Lehman, Kristen E.; Hilger, Hartmut H.; Miller, James S.; Mittelbach, Moritz; Nazaire, Mare; Nepi, Massimo; Nocentini, Daniele; et al.
Abstract: The Boraginales are now universally accepted as monophyletic and firmly placed in Lamiidae. However, a consensus about familial classification has remained elusive, with some advocating recognition of a single, widely variable family, and others proposing recognition of several distinct families. A consensus classification is proposed here, based on recent molecular phylogenetic studies, morphological characters, and taking nomenclatural stability into consideration. We suggest the recognition of eleven, morphologically well‐defined and clearly monophyletic families, namely the Boraginaceae s.str., Codonaceae, Coldeniaceae fam. nov., Cordiaceae, Ehretiaceae, Heliotropiaceae, Hoplestigmataceae, Hydrophyllaceae, Lennoaceae, Namaceae, and Wellstediaceae. Descriptions, synonomy, a taxonomic key, and a list of genera for these eleven families are provided, including the new family Coldeniaceae (monogeneric) and Namaceae (segregated from Hydrophyllaceae and comprising Nama, Eriodictyon, Turricula, and Wigandia ), the latter necessitating a revised circumscription of a more morphologically coherent Hydrophyllaceae.